2016
DOI: 10.1016/j.buildenv.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

An empirical model to predict the performance of typical solar chimneys considering both room and cavity configurations

Abstract: The solar chimney is a reliable passive ventilation system that can largely reduce the energy requirements with both low costs and maintenance for buildings to overcome the current energy crisis. To optimize its design, an empirical model is developed to predict the performance of typical solar chimneys considering both room and chimney cavity configurations using easily acquired inputs. Fire Dynamics Simulator (FDS) as an excellent and open-source tool to solve heating, ventilation and air conditioning proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Each scenario with a simulation time of 900 seconds is enough to allow the full development of the smoke in the tunnel, while the ambient temperature is set at 20°C and the pressure at 101.325 kPa. More details on the numerical methodology of FDS can refer to previous studies …”
Section: Numerical Methodologymentioning
confidence: 99%
“…Each scenario with a simulation time of 900 seconds is enough to allow the full development of the smoke in the tunnel, while the ambient temperature is set at 20°C and the pressure at 101.325 kPa. More details on the numerical methodology of FDS can refer to previous studies …”
Section: Numerical Methodologymentioning
confidence: 99%
“…Referring to the parameterization studies on the various aspects mentioned in Section 2, researchers verified the influence of control parameters on the performance of independent solar chimneys and extended the solar chimney practice to the field of fire prevention and smoke control. Shi et al [48,49] developed empirical models to predict the airflow rate through the air inlets under natural ventilation and smoke exhaustion. The effect of interaction mechanisms between the air inlet and the room window on the performance of the solar chimney was investigated.…”
Section: Work Have Been Done At Rmit University Australiamentioning
confidence: 99%
“…Through different research methods, Dr. Shi has made significant contributions to solar chimney research and promotion. Shi et al [48] conducted the parametric analysis considering installation methods, room/chimney configuration, and cavity materials, thus Through different research methods, Dr. Shi has made significant contributions to solar chimney research and promotion. Shi et al [48] conducted the parametric analysis considering installation methods, room/chimney configuration, and cavity materials, thus developing the empirical models with the assistance of a fire dynamics simulator (FDS) to predict typical solar chimney performance.…”
Section: Work Have Been Done At Rmit University Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that most of them have ignored the impacts from the connected chamber ( i.e. , the room), which results in overestimation [14] . The solar chimney is usually adopted with multiple openings ( i.e.…”
Section: Introductionmentioning
confidence: 99%